Feminist Life Stories: Twelve Journeys Come Together at a Women's Center - Donna Jones-Ilsley (Adult Education Research Conference, 1999)
This study explores the personal narratives of twelve self-proclaimed feminists who started a women's center in a small conservative mid-west town. Our common "herstories" are not identical but reveal learning experiences imbedded in our social and cultural contexts. These social and cultural contexts, however varied, held common threads of the pedagogies we experienced in formal and informal settings. These pedagogies held traditions that are often passed on without question because we are not always aware of their presence. The stories allowed us to reflect on the traditions in our lives in order to come to terms with our past and present realities. As we each learned to be girls, women and feminists, we accepted the rewards of connection and acknowledged the struggle for self-definition. This research chronicles the learning journeys we each took as we came of age in the 50s, 60s, and 70s.